Analysis of Water Quality around Samarinda State Agricultural Polytechnic with Parameters of TDS, pH, COD, Fe, and Zn - Andi Gita Tenri Sumpala; Taufiq Rinda Alkas; Christopaul Pala'langan Toding Layuk; Noorhamsyah; Intan Nur Aini; Endang Fitriani; Tatiya Mulya Sari; Erlanda Yuliana (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2025)
Environmental conditions and community activities impact surface water and groundwater quality. Physical, chemical, and biological parameters can be used to assess water quality so that i can be used by established quality standars. This study aimed to assess the quality of surface water and groundwater around the Samarinda State Agricultural Polytechnic using TDS, pH, COD, Fe, and Zn parameter sat eight different sampling locations. Water quality assessment based on physical and chemical parameters follows the guidelines of Goverment Regulation No. 22 of 2021. Based on the research results, the TDS value range is 61 mg/L – 320 mg/L; the pH value range is 5,4 – 7,97; the COD value range is 136 mg/L – 208 mg/L; the Fe value range is between 21,4 mg/L and 27,3 mg/L, and the Zn value range is between 0,89 mg/L and 1,44 mg/L. This indicates that some water quality parameters, including COD, Fe, and Zn, do not meet the quality limits set by Government Regulation No. 22 of 2021.